The balance between individual liberty and the government’s duty of security: identifying Michel Foucault’s means of correct training in Juli Zeh’s Corpus delicti - McCullough, Dylan (Kansas State University, 2021)
During the recent global pandemic, the balance between individual liberty and the government’s duty to protect its citizens has become an international topic of debate. The primary aim of this project was to explore this balance as it is depicted in Juli Zeh’s not-too-distant medical dystopian novel Corpus Delicti: Ein Prozess. An area of analytical focus that is lacking on this contemporary novel is the discussion of biopower and how those who wield power in health crises behave. Michel Foucault’s text Discipline and Punish offers the theoretical framework to identify those who exercise biopower in an extreme example of authoritarianism. By no means a comparison to what we continue to experience in today’s pandemic, the project does aim to identify actions and ideas to avoid in order to maintain a healthy balance between liberty and protection.
Keywords: Corpus delicti; Michel Foucault; Juli Zeh; Means of correct training